An accountability framework to promote healthy food environments. Issue 11 (25th February 2014) - Kraak, Vivica I; Swinburn, Boyd; Lawrence, Mark; Harrison, Paul
Abstract: Objective: To review the available literature on accountability frameworks to construct a framework that is relevant to voluntary partnerships between government and food industry stakeholders. Design: Between November 2012 and May 2013, a desk review of ten databases was conducted to identify principles, conceptual frameworks, underlying theories, and strengths and limitations of existing accountability frameworks for institutional performance to construct a new framework relevant to promoting healthy food environments. Setting: Food policy contexts within high-income countries to address obesity and diet-related non-communicable diseases. Subjects: Eligible resources ( n 26) were reviewed and the guiding principles of fifteen interdisciplinary frameworks were used to construct a new accountability framework. Results: Strengths included shared principles across existing frameworks, such as trust, inclusivity, transparency and verification; government leadership and good governance; public deliberations; independent bodies recognizing compliance and performance achievements; remedial actions to improve accountability systems; and capacity to manage conflicts of interest and settle disputes. Limitations of the three-step frameworks and 'mutual accountability' approach were an explicit absence of an empowered authority to hold all stakeholders to account for their performance. Conclusions: We propose a four-step accountability framework to guide government and food industry engagement to address unhealthy food environments as part of a broader government-led strategy to address obesity and diet-related non-communicable diseases. An independent body develops clear objectives, a governance process and performance standards for all stakeholders to address unhealthy food environments. The empowered body takes account (assessment), shares the account (communication), holds to account (enforcement) and responds to the account (improvements).